Kyrgyz Republic Public Expenditure Review Policy Notes : Social Assistance - World Bank (Washington, DC, 2014)
This note proposes a reform agenda to address the challenges facing the system of social assistance This will require: i) a progressive shift of public expenditure toward pro-poor programs; ii) improving coherence and complementarity among social protection programs, and iii) making social assistance programs more inclusive and responsive. The structure of this chapter is as follows. The next two sections provide an overview of poverty and the composition and trends in non-contributory social protection expenditure in the Kyrgyz Republic. The fourth section looks at performance of the social assistance expenditure in the Kyrgyz Republic and shows that while spending has increased significantly in recent years, its performance in terms of coverage and targeting of the poor, as well as in terms of its impact on poverty remains modest. Other issues, which are important to take into account in the process of improving effectiveness of social assistance expenditure, are discussed in the following section. The last section concludes by summarizing key challenges and proposing recommendations for system reform, as well as areas requiring further research and analysis.